STUDI PENERAPAN SNI OLEH LEMBAGA PENILAIAN KESESUAIAN - Muti Sophira Hilman; Ellia Kristiningrum (Badan Standardisasi Nasional, 2007)
Conformity assessment body (CAB) such as Certification body, inspection and laboratorium has role in quality assurance of goods or services. Application of SNI by CAB may describe development of standard application. At this time, data of SNI application and its constraint by CAB is not known for sure yet. The objective of the research is to know how many SNI has implemented by CAB and reasons and problems that faced CAB in order to implement SNI. Method of the study is a survey method. Discussion in this study using decriptive method, it describes about situation or factual condition. Data collecting tools is by quetioner. Questioner was distributed to CAB that was accredited by KAN, such as testing laboratory, quality system certification body, environmental quality system certification body, product certification body, calibration laboratory and inspection body. Applying of SNI by LPK is equal to 14.46% SNI applied to amount of total SNI. Amount of SNI applied by testing laboratory is 873 SNI, by calibration laboratory is 210 SNI, 31 SNI applied by inspection body, 134 SNI applied by product certification body, 52 SNI applied by quality management system certification body, 4 SNI applied by HACCP certification body and 5 SNI applied by EMS certification body. The first reason that CAB is not apply SNI that is SNI inappropriate with customer or market need. Cost of treatment and equipments and difficulty of the process accreditation is a major problem of CAB to apply SNI.